Calibration of digital compact cameras for sky quality measures. (November 2020) - Fiorentin, Pietro; Bertolo, Andrea; Cavazzani, Stefano; Ortolani, Sergio
Highlights: Use of smartphone cameras to perform sky photometry. A calibration allows to transfer data from the proprietary RGB color space to a standard color space. Measurement of sky luminance according SI has an uncertainty of about 20%. The colorimetric calibration allows to measure the correlated color temperature of the sky. Calibrated smartphone cameras can be a worldwide distributed tool for sky quality measurements and citizen science activities. Abstract: This work presents the possibility of using the extremely popular compact digital cameras of smartphones or action cameras to perform sky photometry. The newest generation of these devices allows to save raw images. They are not as good as digital single-lens reflex camera, in particular in terms of sensitivity, noise and pixel depth (10 bit versus 12 bit or more), but they have the advantage of being extremely widespread on the population and relatively cheap. These economical digital compact cameras work with an electronic shutter, it overcomes the consumption of mechanics and allows to gather images for long time. The work uses a simple calibration method to transfer raw data from the proprietary RGB color space to the standard CIE 1931 color space. It allows the measurement of sky luminance in cd m −2 with an expected uncertainty of about 20%. Furthermore, the colorimetric calibration allows to know the correlated color temperature of a portion of the sky, it can help the identification of the kind of polluting sources. Aiming at better clarifying the performances of calibrated digital compact cameras, a comparison with a calibrated DSLR camera is presented in outdoor situations showing a good agreement both for luminance and color temperature measurements.